Diagnostic value of serum KL-6 and IL-6 levels in critically ill patients with COVID-19-associated pneumonia. Issue 5 (November 2022) - Kim, Si-Ho; Kyu Cho, Hyun; Jeon, Chun-Hoo; Sung Ock, Hye; Shin, Beomsu; Wi, Yu Mi
Highlights: The role of KL-6 and IL-6 for predicting mortality in critically ill COVID-19 patients was studied. Peak KL-6 and IL-6 levels were elevated in deceased COVID-19 patients. In multivariable analysis, peak KL-6 ≥ 1019.2 U/mL was associated with mortality. Increase in KL-6 level 1 week after admission was significantly higher in the deceased group. Serum KL-6 and IL-6 levels could predict mortality in critically ill COVID-19 patients.